FGF9 variant in 46, XY DSD patient suggests a role for dimerization in sex determination. Issue 3 (28th November 2022) - Croft, Brittany; Bird, Anthony D.; Ono, Makoto; Eggers, Stefanie; Bagheri‐Fam, Stefan; Ryan, Janelle M.; Reyes, Alejandra P.; van den Bergen, Jocelyn; Baxendale, Anne; Thompson, Elizabeth M.; Kueh, Andrew J.; Stanton, Peter; et al.
Abstract: 46, XY gonadal dysgenesis (GD) is a Disorder/Difference of Sex Development (DSD) that can present with phenotypes ranging from ambiguous genitalia to complete male‐to‐female sex reversal. Around 50% of 46, XY DSD cases receive a molecular diagnosis. In mice, Fibroblast growth factor 9 (FGF9) is an important component of the male sex‐determining pathway. Two FGF9 variants reported to date disrupt testis development in mice, but not in humans. Here, we describe a female patient with 46, XY GD harbouring the rare FGF9 variant (missense mutation), NM_002010.2:c.583G > A;p.(Asp195Asn) (D195N). By biochemical and cell‐based approaches, the D195N variant disrupts FGF9 protein homodimerisation and FGF9‐heparin‐binding, and reduces both Sertoli cell proliferation and Wnt4 repression. XY Fgf9 D195N/D195N foetal mice show a transient disruption of testicular cord development, while XY Fgf9 D195N/− foetal mice show partial male‐to‐female gonadal sex reversal. In the general population, the D195N variant occurs at an allele frequency of 2.4 × 10 −5, suggesting an oligogenic basis for the patient's DSD. Exome analysis of the patient reveals several known and novel variants in genes expressed in human foetal Sertoli cells at the time of sex determination. Taken together, our results indicate that disruption of FGF9 homodimerization impairs testis determination in mice and, potentially, also in humans in combination with other variants. Abstract : Immunofluorescence analysis in a FGF9 ‐D195N mouse model: XY Fgf9 D195N/− mice show partial gonadal sex reversal, expressing the meiotic germ cell marker γH2AX (b) and the ovarian somatic cell marker FOXL2 (d). XY Fgf9 +/− mice were used as controls (a, c). AMH is a marker of testicular Sertoli cells. Scale bars 100 μm.